Pengembangan Video Tutorial Sebagai Penuntun Praktikum Bioteknologi Untuk Siswa Sekolah Menengah Atas : (The Development of Videos Tutorial as a Biotechnology Practicum Guide for High School Students) - Dewi Safitri; Suraida Suraida; Reni Safita; Boby Syefrinando; Mainingsih Mainingsih (BIODIK, 2023)
The purpose of this study was to design a video tutorial as a valid, practical, and effective biotechnology practicum guide developed for high school students (SMA).Â  This type of research is R&D (Research and Development) with a 4D model (Define, Design, Development, and disseminate) This type of research is R&D (Research and Development) with the 4D model (Define, Design, Development, and Disseminate) which is limited to stage three.Â  The instrument used in this research is a questionnaire.Â  This research was conducted at MAN 1 Tanjung Jabung Timur on the subject of biology with a limited scale.Â  The analysis is carried out in the form of curriculum analysis, teacher needs analysis, student needs analysis and student characteristics analysis.Â  The assessment was carried out by three experts, namely material experts with a percentage of 89.5%, linguists with a percentage of 87.5% and design experts with a percentage of 95%.Â  The tutorial video was tested with the teacher's response with a percentage of 92.2%.Â  Then the video tutorial was tested on class XII semester II students with a practicality percentage of 97.9%, then the teacher's practicality level was 92.2%.Â  These results indicate that the product developed is declared "very practical".Â  The effectiveness test was given to the same students with a percentage of 92.2% and was declared "very effective."Â  learning.Â  The author proposes suggestions for developing this product with a wider scope or in other materials, even in other subjects in the future. Abstrak. Penelitian ini bertujuan untuk mendesain video tutorial sebagai penuntun praktikum bioteknologi yang valid, praktis, dan efektif yang dikembangkan untuk siswa Sekolah Menengah Atas (SMA). Jenis penelitian R&D (Research and Development) dengan model 4D (Define, Design, Development, and Disseminate) yang dibatasi hanya sampai tahap ke tiga. Instrumen yang digunakan pada penelitian ini adalahÂ  berupa angket. Penelitian ini dilakukan di MAN 1 Tanjung Jabung Timur pada mata pelajaran biologi dengan skala terbatas. Analisis yang dilakukan berupa analisis kurikulum, analisis kebutuhan guru, analisis kebutuhan siswa dan analisis karakteristik siswa. Penilaian dilakukan oleh tiga ahli yaitu ahli materi dengan persentase 89,5%, ahli bahasa dengan persentase 87,5% dan ahli desain dengan persentase 95%. Video tutorial diujicobakan respon guru dengan persentase 92,2%. Kemudian video tutorial diujicobakan kepada siswa kelas XII semester II dengan persentase praktikalitas 97,9%, kemudian tingkat praktikalitas guru sebesar 92,2%. Hasil ini menunjukan bahwa produk yang dikembangkan dinyatakan â€œ sangat praktisâ€. Untuk ujicoba efektivitas diberikan kepada siswa yang sama denganÂ  persentase sebesar 92,2% dan dinyatakan â€œsangat efektifâ€ Berdasarkan hasil penelitian maka dapat disimpulkan bahwa pengembangan Video Tutorial Sebagai Penuntun Praktikum Bioteknologi Untuk Siswa Sekolah Menengah Atas sangat valid, praktis dan efektif untuk digunakan dalam proses pembelajaran.Â